The future of technological civilization - Ferkiss, Victor (G. Braziller, 1974)
George Braziller Inc. Hardcover 1974 First Printing. 370 pp. Size 9.5" by 6.5" by 1.5". DJ shows shelf wear in that front top edge is somewhat sun-darkened and top of spine is slightly tattered. Binding intact; no loose pages. Covers and pages are clean and unmarked. In excellent condition.